Hiszpania jako miejsce schronienia opozycji w okresie pierwszej wojny domowej i dyktatury Lucjusza Korneliusza Sulli (88–79 p.n.e.) - Ładoń, Tomasz (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
During the First Civil War and the dictatorship of Lucius Cornelius Sulla, Spain was one of the main directions of political emigration. The author of the article distinguished three stages. The first occurred immediately after the outbreak of the First Civil War in 88 BC. A small group of refugees escaped from the repression of Sullan to Spain. The second stage involved the escape from the Marian repression that broke out in Rome after Sulla’s departure to the war with the Mithridates. The third stage of emigration to Spain followed the victory of Lucius Cornelius Sulla in the First Civil War in Italy and the introduction of proscription (82 BC). The Iberian Peninsula for the defeated Marians became not only the main direction of escape from repression, but also a center of opposition to the rulers of Rome.